Bad blood - Fairstein, Linda A. 1947- (Sphere, 2009)
Alexandra Cooper has a tough case to prosecute. Brendan Quillian, a wealthy businessman from the Upper East Side, has been charged with hiring an assassin to kill his wife, but the evidence is flimsy and the defendant has one of the most successful defence lawyers on his side. Then an explosion in one of the tunnels being built to secure Manhattan's water supply kills Quillan's brother, one of the construction workers. The blast isn't terrorism, it isn't an accident and it looks as though Duke Quillian was the target. And none of the team investigating the murder had come across any hint that Brendan had a brother, never mind one so far on the other side of the tracks. With another case to solve, Alex, together with Detectives Chapman and Mercer, discover that Quillan's upbringing is very different from what they'd assumed, and within the cupboard of his estranged family there are many skeletons, not all of them metaphorical. In a cliff-hanging whodunnit, Linda Fairstein takes the reader on a roller-coaster ride through New York and deep beneath its streets, to a conclusion which is as surprising as it is frightening.